The design of inducement prize contests for research and innovation - Moore, M (2013)
Inducement prize contests, where a monetary prize is offered for a specified technological achievement, are increasingly popular means of incentivising research and innovation. Such prizes are often modelled by the rent-seeking Tullock contest, or an all-pay auction. However, the direct application of such models can overlook some particular features of technological competition. This thesis addresses three such features. The first model notes that preliminary prizes are often part of contest designs. A two-round Tullock model is used to investigate a potential motivation for offering such prizes when contestants have different productivities. A designer can identify and purchase the rights to the more productive technology where the award of the preliminary prize is conditional on the winner licensing his technology to other contestants. In this way, endowing a preliminary round results in the potential for increased second round productivity, but at the cost of a reduced second round prize. Such a structure is optimal when the productivities are sufficiently different. In the second model, it is noted that expenditures in inducement prize contests are often too large to be explained by the cash prize alone. There usually exists a final consumer application of the research. This chapter examines how different types of prizes arise by considering the informational content of winning and the effect this has on quality differentiation in when there is an established quality leader. A purely informational 2 prize influences investment decisions and also the qualities offered in the market. The main result is that some prizes may aim to select the highest quality firm as often as possible, whereas other prizes may aim to reward the entrant only if a significant improvement in quality is made. In the third model, prizes are not the only instruments available to contest designers. In particular, subsidy of spending may be possible. This chapter uses an intuitive interpretation of the Tullock contest to offer a matching-funds instrument to a budget constrained principal. It is shown that symmetric prize/subsidy contest designs may be optimal even in the context of contestant asymmetry, in contrast to most existing contest design models. It is also shown that if only one subsidy is offered, it is always to the weaker contestant. The role of contest accuracy in these findings is also considered